First isolations of Thraustochytriales (Labyrinthulomycetes, Heterokonta) from estuarial and saline environments of Argentina - Rosa, S.M. (2006)
This is the first report of Labyrinthulomycetes for Argentina. Five strains of Thraustochytriales were isolated from both, a saline continental environment and an estuarial one from Argentina. The strains were identified as Thraustochytrium aff. antarcticum, Ulkenia aff. radiata and U. aff. visurgensis because the observations did not exactly fit the original descriptions in the morphological and ecological aspects.